2014
DOI: 10.1097/igc.0000000000000201
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Review of Primary Non-Hodgkin Lymphoma of the Female Genital Tract: A 33-Year Experience

Abstract: Our report is the largest published single-institution experience of this disease. It demonstrates a more favorable prognosis and proposes that with early diagnosis and appropriate therapy, radical gynecologic surgery can be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 19 publications
(36 reference statements)
2
40
0
Order By: Relevance
“…Ahmad et al . (24) reported a more favorable prognosis in these patients, while a study from China showed that these patients had a high risk of CNS relapse and therefore had poorer prognosis (25). These issues definitely require comprehensive cooperation to achieve accurate insight into these rare extranodal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Ahmad et al . (24) reported a more favorable prognosis in these patients, while a study from China showed that these patients had a high risk of CNS relapse and therefore had poorer prognosis (25). These issues definitely require comprehensive cooperation to achieve accurate insight into these rare extranodal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This is evident in our case series, as it was seen in 3 of our patients. In general, B-cell lymphomas have a better prognosis and overall response to traditional treatment than T-cell lymphomas (Ahmad et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…In our case series, 2 patients out of the 5 reported weight loss and only one experienced malaise. In a recent study of 36 patients with Non-Hodgkin's lymphoma originating in gynecological organs, only 17% patients have such constitutional symptoms (Ahmad et al, 2014). The most common presentation in this large review was vaginal bleeding and enlarging pelvic mass (Ahmad et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical diagnosis of primary uterine lymphoma can be challenging, partly because affected patients are often asymptomatic or only have nonspecific symptoms. Of 36 patients diagnosed with non‐Hodgkin's lymphoma of the female genital tract in Yale‐New Haven Hospital, 11% were asymptomatic, 24% presented with vague abdominal complaints, and 14% had constitutional symptoms such as fever, night sweats, and weight loss . Another report concluded that the most common initial presentations are vaginal bleeding or discharge, abdominal or pelvic pain, and rarely urinary obstruction .…”
Section: Discussionmentioning
confidence: 99%